Community Development Banks - Hyman P. Minsky; Dimitri B. Papadimitriou; Ronnie J. Phillips; L. Randall Wray (Levy Economics Institute of Bard College, 1992)
The Clinton/Gore proposal for the creation of a network of 100 community development banks (CDBs) to revitalize communities is bold, and will contribute to the success of the U.S. economy. Banks are essential institutions in any community, and the establishment of a bank is often a prerequisite for the investment process. For this reason, the creation of banks in communities lacking such institutions is important to the welfare of these communities. The vitality of the American economy depends on the continual creation of new and initially small firms. Because it is in the public interest to foster the creation of new entrants into industry, trade, and finance, it is also in the public interest to have a set of strong, independent, profit-seeking banking institutions that specialize in financing smaller businesses. When market forces fail to provide a service that is needed and potentially profitable, it is appropriate for government to help create the market. Community development banks fall into such a category. They do not require a government subsidy, and after start-up costs, the banks are expected to be profitable. The primary perspective of this concept paper is that the main function of the financial structure is to advance the capital development of the economy-to increase the real productive capacity and wealth-producing ability of the economy. The second assumption is that capital development is encouraged by the provision of a broad range of financial services to various segments of the U.S. economy, including consumers, small and large businesses, retailers, developers, and all levels of government. The third is that the existing financial structure is particularly weak in servicing small and start-up businesses, and in servicing certain consumer groups. The fourth is that this problem has become more acute because of a decrease in the number of independent financing alternatives and a rise in the size distribution of financing sources, which have increased the financial system's bias toward larger transactions. These are assumptions that appear to be supported by the evidence: they are also incorporated in other proposals that advance programs to develop community development banking.
Keywords: 330